Medjora Cafe Public Relations Campaign in Building Brand Image As An Eco-Friendly Cafe / Kampanye Public Relation Medjora Cafe Dalam Membangun Brand Image Sebagai Kafe Eco-Friendly - Mei Candra Mahardika; Sari, Maya Candra (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2025)
Medjora Cafe carries an environmentally friendly concept. This is based on environmental problems regarding waste in Kemuning Village, Karanganyar Regency. Medjora Cafe implements policies to campaign for public relations in handling environmental problems, especially waste among the culinary industry in Karanganyar Regency. Data collection by interview, observation and various documentation at Medjora Cafe. Medjora Cafe in implementing campaign communication about environmental problems, by reducing plastic straws replaced with stainless steel straws, tissue replaced with cloth and the use of used goods to be used as ornaments and decorations in the cafe. The use of Instagram as a campaign media as well as to build a brand image, this application is considered to be widely used by the public and customers so that the objectives in the campaign to build a brand image as an eco friendly cafe can be accepted by the wider community. The main campaign message from Medjora Cafe is to inform ideas about the environment, namely greenhouses and eco friendly. Contributions in public relations campaigns regarding environmental issues in addition to providing knowledge to the public and education in order to protect the surrounding environment. The preparation of a public relations campaign carried out by Medjora Cafe is also to introduce the 3R concept, namely Reduce, Reuse and Recycle. Apart from being a campaign to protect the environment, the 3R concept is proof of Medjora Cafe being an eco-friendly cafe as its brand image.